2023
DOI: 10.3390/genes14071364
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Breast Cancer: An Old Story with a New End

Abstract: Breast cancer is the second most frequent cancer in the world. It is a heterogeneous disease and the leading cause of cancer mortality in women. Advances in molecular technologies allowed for the identification of new and more specifics biomarkers for breast cancer diagnosis, prognosis, and risk prediction, enabling personalized treatments, improving therapy, and preventing overtreatment, undertreatment, and incorrect treatment. Several breast cancer biomarkers have been identified and, along with traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 236 publications
1
15
0
Order By: Relevance
“…The high prevalence rate of breast cancer has aroused women’s great attention. 17 , 18 Breast cancer has a convoluted development mechanism in addition to a high incidence rate, bad prognosis, and major effects on women’s ability to lead healthy lives. 19 , 20 With the deepening of lncRNA research, more and more lncRNAs have been found to play important roles in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence rate of breast cancer has aroused women’s great attention. 17 , 18 Breast cancer has a convoluted development mechanism in addition to a high incidence rate, bad prognosis, and major effects on women’s ability to lead healthy lives. 19 , 20 With the deepening of lncRNA research, more and more lncRNAs have been found to play important roles in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical models not only reflect intra-tumoral heterogeneity and account for variance in the landscape of the microenvironment but must also mirror the intra-tumoral heterogeneity observed amongst patients. Many factors play a critical role in the onset and progression of breast cancer, including genetic background [ 97 ]. Specific population subsets within the population at large have a genetic predisposition to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing focus on molecular prognostic tests in recent times, there is a tendency to disregard the crucial role played by traditional clinical and pathological factors in predicting breast cancer prognosis [15]. In the era of advanced molecular diagnostic tests, the traditional factors still remain essential in determining prognosis and guiding therapeutic decisions for individuals facing a new diagnosis of invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%